Yhdeksän taiteilijaa - Kivirinta, Marja-Terttu (WSOY, 2007)
Summary
Keywords: Ahtila, Eija-Liisa; Brotherus, Elina; Kaikkonen, Kaarina; Kanervo, Marja; Liukko, Rauni; Liulia, Marita; Rantanen, Mari; Ryöppy, Catarina; Wirkkala, Maaria; kuvataide; installaatiot; elokuvataide; valokuvataide; ympäristötaide; tilataide; kuvanveisto; verkkotaide; interaktiivinen taide; multimedia; maalaustaide; kuvataiteilijat; naiset; Suomi